Monitoring episodes of falling in an institution for the elderly - Cristina Lavareda Baixinho; Maria dos Anjos Dixe (Universidade Federal de Goias, 2014)
Falls cause impairment, dependency and isolation, increase comorbidity, and are the main cause of death by accident among the elderly. This descriptive study was performed through a document analysis, with the objective to identify the prevalence rate, incidence and characteristics of episodes of falling among elderly residents of an institution. Data were collected from 6,205 institutional records using a semi-structured instrument, and analyzed by descriptive statistics. A total 123 episodes of falling were identified. Of the 99 elderly subjects, 40.9% suffered at least one fall, 23 of which had two or more episodes. Women and the eldest patients fall more often, mostly at night and in their room, when they get up. Most situations did not result in injuries. Safety measures can prevent falls or their recurrence. Improving the quality of records of falls can help the systematic monitoring of these episodes and improve the quality of nursing care. Descriptors: Homes for the Aged; Accidental Falls; Nursing Care.